Mobilizing Social Capital in Social Entrepreneurship: Strategies, Networks, And Growth in The Egyptian Context - Alaa, Doaa (AUC Knowledge Fountain, 2026)
This thesis examines how social entrepreneurs in Egypt strategically mobilise social capital to access resources, legitimacy, and opportunities within a fragmented and institutionally ambiguous ecosystem. Drawing on qualitative case studies of eight legally registered, mission-driven for-profit enterprises, the study analyses how founders build and leverage offline and online networks through practices such as emotional bonding, community formation, knowledge sharing, symbolic positioning, ecosystem engagement, and digital presence. Through thematic analysis of semi-structured interviews and secondary data, the research identifies a set of relational strategies that function as core mechanisms for entrepreneurial growth in contexts where formal support structures and legal definitions remain limited. The findings contribute to social entrepreneurship scholarship by offering a grounded explanation of how social capital is actively constructed and deployed in an emerging-market setting, highlighting the centrality of relational work to entrepreneurial trajectories. The study also offers implications for Social Enterprise Support Organizations (SESOs), policymakers, donors, and founders seeking to strengthen the relational infrastructures of Egypt’s social enterprise ecosystem.